2020
DOI: 10.1002/jor.24925
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of a modified proximal humeral locking plate application for distal extra‐articular diaphyseal humeral fractures

Abstract: The extra-articular distal humerus locking plate (EADHP) is widely used for distal extra-articular diaphyseal humeral fracture fixation. However, it occasionally causes skin prominence and discomfort. The upside-down use of a proximal humerus internal locking system (PHILOS) plate is suggested as an alternative option, but it lacks biomechanical evidence. The purpose of this study was to compare the biomechanical performance between two different fixation methods: the modified use of the PHILOS plate on the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…The simulation results of the EADHP and PHILOS are summarized in Table 3 . As in a previous biomechanical study using cadavers 18 , the EADHP and PHILOS exhibited adequate biomechanical performance and stability under axial, bending and varus load conditions. The maximum von-Mises stress of the EADHP on the plate was 300.54 MPa under the axial force, while those of the PHILOS were 109.62 MPa and 83.63 MPa on the humerus under the bending and varus forces, respectively.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The simulation results of the EADHP and PHILOS are summarized in Table 3 . As in a previous biomechanical study using cadavers 18 , the EADHP and PHILOS exhibited adequate biomechanical performance and stability under axial, bending and varus load conditions. The maximum von-Mises stress of the EADHP on the plate was 300.54 MPa under the axial force, while those of the PHILOS were 109.62 MPa and 83.63 MPa on the humerus under the bending and varus forces, respectively.…”
Section: Resultssupporting
confidence: 76%
“…In the 30 mm space, at least four locking screws can be used to perform distal fixation on the anterior plating with the PHILOS. The 10 mm gap was aimed at causing extreme instability in a biomechanical DHSF model 14 , 18 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immobilization is often required in the early postoperative period, thus losing the opportunity of early functional exercise. Many studies [17,18] have shown through biomechanical analysis that a single plate is suitable for fracture types of the middle and upper part of the humerus, while a double plate and double column xation can provide better antibending and anti-torsion forces for fractures of the distal humerus. Since the fracture characteristics of the distal third diaphyseal fracture of the humerus determine if the distal end of the fracture is xed with a single plate, it is di cult to achieve with three screws and six cortical xations, and therefore, the xation can be unstable.…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff value was 60.5 mm for distal humeral width, which corresponds to a sensitivity of 100% and a specificity of 81.8%. pared to EADHP [21]. Yin et al [22] suggested both an anterolateral approach and a lateral approach to distal humeral extra-articular fractures as alternative surgical methods.…”
Section: Discussionmentioning
confidence: 99%